Efficacy of Insecticides Against Pieris brassicae nepalensis (Doubleday) on Cabbage in Chitwan, Nepal - Gautam, Bhola; Tiwari, Sundar; Thapa, Resham Bahadur (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
A field experiment was conducted to test the efficacy of microbial, botanical, safe chemical insecticide and some other potentially dangerous chemical insecticide against cabbage butterfly Pieris brassicae nepalensis (Doubleday) in cabbage under field condition. Six different commercially available pesticide: 1) Spinosad @ 0.2 ml/liter (Tracer 45% SC, semi-microbial), 2) Neemix 300 ppm @ 2ml/liter (Commercial product of neem), 3) Mahashakti @ 2ml/liter (Formulation of B. thuruingenesis), 4) Malathion 50% WP @ 2 ml/liter (safe chemical pesticide), 5) Dichlorvos 76% EC @ 1ml/liter (unsafe chemical pesticide), 6) Emamectin benzoate 5% SG @ 0.2 gm/l (bio- insecticide), and 7) Control were applied comprising 7 treatments and three replications. Cabbage variety Green Coronet was planted in plots of 3m × 3m with spacing of 40 cm × 40 cm in a randomized complete block design. Data collection regarding pests and natural enemies were done at 3, 6 and 9 days after spray. The results obtained from different treatments against cabbage butterfly showed that Diclorovus, Emamectin benzoate and Spinosad were the most effective and consistent in controlling larval population of Pieris brassicae nepalensis. Three insecticides [Diclorovus (87.56%), Emamectin benzoate (80.31%) and Spinosad (72.44%)] gave highly significant protection of cabbage butterfly over control all the time in all three sprays. The treatments Malathion (45.38%), B.t (38.08%) and Neemix (48.35%) failed to give significant reduction of larval population after 1st spray; however, after 2nd and 3rd spray all six treatments gave significant protection from cabbage butterfly larvae over control. Besides chemical pesticide Dichlorovus, Bio-Pesticides such as Emamectin benzoate and Spinosad were found to give effecient control over cabbage butterfly thus can be used as substitute of chemical pesticides for management of Pieris brassicae nepalensis under Chitwan condition.
Keywords: Cabbage butterfly; Pieris brassicae nepalensis; Cabbage; Emamectin benzoate; Spinosad